COMMUNICATIVE-MEDIATORY FUNCTION OF SECONDARY TEXTREVIEWS - Diana Movchan; Galyna Chulanova; Iryna Kobyakova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The present paper deals with English secondary TextReviews, an increasingly popular and non-trivial mode of computer-mediated communication, which provides popularisation of the book itself as well as the increase of motivation to reading. It is considered that TextReviews are oriented on pragmatically focused impact on the reader and perform communicative-mediatory function in society, creating the algorithm of behaviour of potential readers. Particular attention is focused on the role of a reader, whose task is to extract maximum of the author's thoughts, to grasp as much information as possible, to assess the merits of the book and finally to share emotions with potential readers. We have presented and comparatively analysed the linguistic means with the help of which authors of TextReviews manipulate potential readers. The study relies on such methods as textual analysis, contextual method, interaction analysis, and quantitative method. The results of this research show that audience-oriented type of texts is the most common. Spatio-temporal constraints of impact of TextReviews make their authors create a text in which elements of different levels of language, together with non-verbal components, are to convince the potential readers of the need to commit the actions programmed by the author of the TextReview, i.e. purchase of a book. The paper stipulates that TextReview becomes one of the main strategies of a new approach to the book publishing and book distribution nowadays.